TGFB1 represses the expression of SF1 and LRH1 to inhibit E2 production in rat LCs. Issue 5 (May 2017) - Yang, Qianqian; Ma, Binfang; Qiao, Huilian; Ma, He; Dong, Yuhang; Cao, Liang; Ma, Jing; Li, Zhen
Abstract : Leydig cells (LCs) in the adult testis have been identified as the major sites of oestrogen production, which is crucial for mammalian germ cell differentiation. Our previous work showed that transforming growth factor beta 1 (TGFB1) inhibits estradiol (E2 ) secretion via down-regulating Cyp19 gene expression in mature rat LCs. However, the mechanism remains unclear. In the present study, the effects of TGFB1 on the expression levels of steroidogenic factor 1 (SF1), liver receptor homolog 1 (LRH1), cAMP response element-binding protein (CREB) and cAMP responsive element modulator (CREM) were evaluated both in primary cultured LCs and in rat testis. The involvement of TGFB1 signalling in the regulation of SF1 and LRH1 expression was then validated by applying the inhibitor of the TGFB type 1 receptor (TGFBR1) SB431542. Moreover, the expression of CYP19 in testicular LCs was investigated and the production of E2 in testicular interstitial fluid (TIF) was measured. The results showed that TGFB1 especially down-regulated the expression levels of SF1 and LRH1 both in primary cultured LCs and in rat testis. The down-regulations of TGFB1 in the production of E2 in TIF and the expression of CYP19 in testicular LCs were also observed in vivo . These inhibitory effects could be reversed by TGFBR1 inhibitor SB431542. Our findings suggest that TGFB1 may act through the canonical signalling pathway involving ALK5 to restrain SF1 and LRH1 accumulation and eventually attenuate Cyp19 transcription and oestrogen production in LCs.